Meniscofibular ligament - Narrative review of anatomy, biomechanics, imaging, physical examination and clinical importance - Marcin Mostowy; Dawid Ciechanowicz; Marcin E. Domżalski (Elsevier, 2021)
Introduction: Meniscofibular ligament (MFibL) is relatively unknown structure of posterolateral corner of the knee (PLC). In the last years some authors considered MFibL to be important structure playing a role in the biomechanics of lateral meniscus (LM). The aim of the study was to review the literature concerning MFibL anatomy, biomechanics, imaging, physical examination and clinical importance of this structure. Methods: PubMed, Scopus, Embase and Cochrane Library databases were searched with the following terms: "meniscofibular ligament", "MFibL". Additional relevant studies were sought in the bibliographies of included articles. Decisions concerning screening, inclusion and data extraction were performed independently by two authors of the review. Main findings: MFibL is a thickening of posterolateral capsule of knee joint coursing from the inferior part of the posterior one-third of LM to the head of the fibula. Mean length of MFibL is about 19 mm, mean width proximally 13 mm and mean width distally 8.5 mm. Thickness of MFibL is highly variable ranging from 2.6 to 6.1 mm and may be associated with morphology of proximal tibiofibular joint (PTFJ). It is possible to visualize MFibL on MRI and arthroscopy. MFibL probably plays a role in restricting anterior movement of LM during extension. MFibL biomechanics may be associated with PTFJ morphology, however there are no quantitative biomechanical studies. It is unknown whether its injury influences posterolateral stability of the knee. Up to date there are no distinct physical tests for assessment of MFibL injury. It was proposed to be associated with longitudinal LM injuries. Up to date we did not find studies reporting treatment outcomes apart from one case report. Conclusions: While anatomy and imaging of MFibL are relatively well described, there is still a great paucity of knowledge concerning its biomechanics, physical examination and clinical importance.